139k views
5 votes
Solve for a

Pythagorean theorem

Solve for a Pythagorean theorem-example-1
User KentZhou
by
5.6k points

2 Answers

11 votes


{a}^(2) + {b}^(2) = {c}^(2)


{c}^(2) - {b}^(2) = {a}^(2)


{8}^(2) - {6}^(2) = {28}^(2)


√(28)

User Rich Drummond
by
5.4k points
5 votes

Answer:


\boxed{\sf{a=√(28) }}

Explanation:

Pythagorean theorems can be applied to solve this problem.

Pythagorean theorem:


\rightarrow \sf{a^2+b^2=c^2}

⇒ c²-b²=a²

8²-6²=28²

Solve.

PEMDAS stands for:

  • Parenthesis
  • Exponents
  • Multiply
  • Divide
  • Add
  • Subtract


\sf{8^2-6^2}

Solve by exponents from left to right numbers.


\sf{8^2=8*8=64}


\sf{6^2=36}

Then, subtract.


\sf{64-36=\boxed{\sf{28}}

a=√28

Therefore, the correct answer is a=√28.

I hope this helps you! Let me know if my answer is wrong or not.

User Bill Gribble
by
4.8k points